Ravish me with rubies - Feather, Jane (Feather, Jane. London jewels trilogy, 2021)
Petra Rutherford is certain she isn't the first dreamy-eyed girl that devilishly handsome Baron Granville of Ashton has loved and left behind. But when her brother's political ambitions place her before him once more, she's determined to give Guy Granville his own taste of torment. What better way to best a scoundrel than by luring his interest--before bringing things to an abrupt, embarrassing end? Guy Granville is disarmed by Petra's bold pursuit of him, so much so that he forgets he never intended to fall in love--much less entertain thoughts of marriage. Now, if only the fiery Petra would stop sparring with him long enough to surrender to him completely--and allow him to convince her that his riches, his rubies, and his heart belong with her.